2011
DOI: 10.1007/s11661-011-0618-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated-Temperature Mechanical Behavior of As-Cast and Wrought Ti-6Al-4V-1B

Abstract: This work studied the effect of processing on the elevated-temperature [728 K (455°C)] fatigue deformation behavior of Ti-6Al-4V-1B for maximum applied stresses between 300 to 700 MPa (R = 0.1, 5 Hz). The alloy was evaluated in the as-cast form as well as in three wrought forms: cast-and-extruded, powder metallurgy (PM) rolled, and PM extruded. Processing caused significant differences in the microstructure, which in turn impacted the fatigue properties. The PM-extruded material exhibited a fine equiaxed a + b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Boehlert C J, et al [108] showed that the creep resistance of as-cast Ti-6Al-4V-1B alloy was significantly better than that of Ti-6Al-4V-0.1B alloy, and the steady-state creep rate was, at least, one order of magnitude lower than that of as-cast Ti-6Al-4V alloy. Chen W, et al [109] investigated the as-cast Ti-6Al-2Sn-4Zr-2Mo-0.1Si alloy and showed that the addition of B could also improve the high-temperature creep resistance of the alloy, but the improvement's effect was not as obvious as that of Ti-6Al-4V alloy.…”
Section: Alloy Compositionmentioning
confidence: 99%
“…Boehlert C J, et al [108] showed that the creep resistance of as-cast Ti-6Al-4V-1B alloy was significantly better than that of Ti-6Al-4V-0.1B alloy, and the steady-state creep rate was, at least, one order of magnitude lower than that of as-cast Ti-6Al-4V alloy. Chen W, et al [109] investigated the as-cast Ti-6Al-2Sn-4Zr-2Mo-0.1Si alloy and showed that the addition of B could also improve the high-temperature creep resistance of the alloy, but the improvement's effect was not as obvious as that of Ti-6Al-4V alloy.…”
Section: Alloy Compositionmentioning
confidence: 99%
“…The addition of small amounts of B to Ti2AlNb and TiAl intermetallics and conventional Ti alloys, such as Ti-6Al-4V(wt.%) and Ti-6Al-2Sn-4Zr-2Mo-0.1Si(wt.%), has been shown to significantly decrease the grain size and/or lamellar spacing leading to significant benefits including increasing tensile strength and fatigue and creep resistance [9,20,[41][42][43][44][45][46][47][48][49][50]. In addition, it reduces the time spent on expensive and energy-intensive thermomechanical processing used to 1 henceforth all compositions will be given in atomic percent unless otherwise specified.…”
Section: Introductionmentioning
confidence: 99%